Preservation of the photocatalytic activity of TiO2 by EDTA in the reductive transformation of Cr(VI). Studies by Time Resolved Microwave Conductivity - Meichtry, Jorge Martin (2014)
P25 TiO2 was found to be deactivated after Cr(VI) (0.8 mM) photocatalytic experiments at pH 2 in the absence of EDTA, but this deactivation was not found in the presence of the organic compound (2 mM), which preserves the activity of the photocatalyst. The results were confirmed by TRMC measurements. The preservation of the activity by the presence of EDTA can be a general behavior of reducing oligocarboxylic acids present together with Cr(VI) in the photocatalytic system, where Cr(III) soluble complexes can be formed and Cr(III) deposition onto the TiO2 surface is prevented. The treatment of a set of diluted Cr(VI) solutions (0.8 mM) in successive experiments with the reused photocatalyst was more efficient for Cr(VI) removal in the presence of EDTA (2 mM, 700 s total irradiation time) than the use of a more concentrated sample (Cr(VI), EDTA) with the same photocatalyst submitted to a longer irradiation (900 s), indicating a good strategy for application. A change in the kinetics from a pseudo-first order at the lowest concentration to an almost zero order at the highest concentration takes place and is analyzed.